DESIGN AND THERMAL PERFORMANCE OF MODULAR ISLAMIC ARCHITECTURE USING LOCAL CLIMATE-RESPONSIVE MATERIALS - Sulaiman Sulaiman; Sokha Dara; Ravi Dara (Yayasan Adra Karima Hubbi, 2025)
Contemporary architecture in many Islamic countries faces the dual challenge of preserving cultural identity while addressing energy efficiency and thermal comfort in harsh climatic conditions. This research explores the integration of modular construction with the timeless principles of Islamic architecture and the use of indigenous, climate-responsive materials as a sustainable solution. A prototype of a modular residential unit was designed, incorporating key Islamic architectural elements such as a central courtyard, mashrabiya (ornate lattice screens), and strategic orientation. The design utilized locally sourced materials with high thermal mass, such as rammed earth and reclaimed timber. The thermal performance was rigorously evaluated using computational fluid dynamics (CFD) and dynamic thermal simulations with EnergyPlus software. The simulation results were benchmarked against a conventional modern residential unit of equivalent size. The integration of passive design strategies resulted in a 25% reduction in annual cooling loads. Indoor operative temperatures remained within the comfort zone for 60% longer than the baseline case, substantially minimizing reliance on mechanical air conditioning. The mashrabiya and courtyard proved effective in facilitating natural ventilation and reducing solar heat gain. This study validates that merging modular construction with climate-responsive local materials and Islamic architectural wisdom offers a viable path toward sustainable and culturally resonant architecture.